Effect of an 11-Week Resistance Training Program on Arterial Stiffness in Young Women. Issue 2 (1st February 2023) - Morgan, Brian; Mirza, Ateeb M.; Gimblet, Colin J.; Ortlip, Austin T.; Ancalmo, Juliana; Kalita, Diane; Pellinger, Thomas K.; Walter, Jessica M.; Werner, Timothy J.
Abstract: Morgan, B, Mirza, AM, Gimblet, CJ, Ortlip, AT, Ancalmo, J, Kalita, D, Pellinger, TK, Walter, JM, and Werner, TJ. Effect of an 11-week resistance training program on arterial stiffness in young women. J Strength Cond Res 37(2): 315–321, 2023—The current investigation was conducted to determine the effect of 2 resistance training models on indices of arterial stiffness in young, healthy women. Twenty-four women, untrained college students, aged 18–22 years were randomized into 1 of 3 groups: control (CON) group ( n = 8), high-intensity (HI) resistance exercise group ( n = 8), and high-volume (HV) resistance exercise group ( n = 8). Subjects randomized to resistance training groups were required to perform strength training exercises 3–5 days a week for 11 weeks. The exercise regimen consisted of 2–3 sets of 3–8 repetitions (80–90% of 1 repetition maximum [1RM]) for the HI group and 3–4 sets of 10–15 repetitions (50–70% of 1RM) for the HV group. All subjects were instructed to continue their normal diet and avoid cardiovascular exercise during the study. After the intervention, there was a significant increase in carotid femoral pulse wave velocity (PWV) (6.39 ± 0.73 to 8.40 ± 2.31 m·s −1 ; p < 0.05) and carotid radial PWV (9.77 ± 1.74 to 12.58 ± 2.09 m·s −1 ; p < 0.05) in the CON group alone. Both the HI and HV groups increased their maximum squat (36.6 ± 7.9 vs. 41.3 ± 31.8 percent change; p < 0.05), bench press (34.4 ± 12.6 vs. 23.4 ± 11.1 percent change; p < 0.05), and seated row (22.0 ± 12.6 vs. 21.9 ± 12.5 percent change; p < 0.05), respectively. Our findings support the use of resistance training exercise without undue impact on vascular compliance in otherwise healthy women.